REFERENSI DALAM BAHASA BERITA TELEVISI - Indri Yuliana; Hasnah Faizah; Charlina ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRACT: This research study about reference in television news Ianguage which in form of persona reference, guide reference (demonstrative), and comparability reference. This research use approach qualitative and descriptive method with aim to for mendeskripsikan form reference in television news Ianguage. this Research data amount to 74 steming from 14 news vidio. This research use oral data type which coming from ujaran carrier of news, reporter, guest speaker and journalist. Pursuant to its structure [of] reference him which [is] writer find to consist of three form that is persona form, comparability and demonstrative. Reference in form of persona amount to fourty nine. Reference in form of or indicator of demonstrative amount to twenty four. Reference in form of komperatif amount to one. Reference meaning of tuturan cover sentence having a meaning (of) deklaratif, introgatif, imperative, and empatik. Sentence having a meaning (of) deklaratif amount to six puluh one data, sentence having a meaning (of) interogatif amount to two, sentence having a meaning (of) imperatif amount to four, and sentence having a meaning (of) empatik amount to six. This research in form of structural so that write to analyse from facet of gramatikal division and according to category matching with formula of[is problem of writerKeyword : reference, news Ianguage, and television news.